Anmeldelser - Aktor, Mikael; Albinus, Lars; Jensen, Hans J. Lundager; Kühle, Lene; Markússon, Guðmundur Ingi; Müller, Mogens; Nørager, Troels; Riis, Carsten (Religionsvidenskabeligt Tidsskrift, 2001)
-